Non-Linear Response to Periodic Forcing of Methane-Air Global and Detailed Kinetics in Continuous Stirred Tank Reactors Close to Extinction Conditions. (September 2015) - Marra, Francesco Saverio; Acampora, Luigi; Martelli, Emanuele
This paper focus on the behavior of a continuous stirred tank reactor (CSTR) subject to perturbations of finite amplitude and frequency. Two main objectives are pursued: to determine the extinction line in the equivalence ratio (φ) - residence time (τ) plane, fixed the thermodynamic state conditions; and to characterize the response of the chemical system to periodic forcing of the residence time. Transient simulations of combustion of methane with air, using both global single-step and detailed chemical kinetic mechanisms, have been conducted and the corresponding asymptotic solutions analyzed. Results indicate very different dynamical behaviors, posing the issue of a proper choice of the kinetic scheme for the numerical study of combustion oscillations.